QUALITY OF LIFE AND WORK SATISFACTION OF HIGH SCHOOL TEACHERS IN SLOVAKIA - CHMELAROVA, Zuzana; PREKOPOVA, Jana (Trends in education, 2012)
The article is focused on the quality of life and work satisfaction of high school teachers in Slovakia. The paper describes research results gained by SEIQoL (The Schedule for the Evaluation of Individual Quality of Life) method and by work satisfaction questionnaire. The quality of life reached the value approximately of 68 from 100. The total satisfaction with life is 72. Only 68 % of secondary school teachers are satisfied with their job.
Keywords: quality of life; work satisfaction; high school teachers.